Phosphorus-nitrogen compounds: part 53-synthesis, characterization, cytotoxic and antimicrobial activity, DNA interaction and molecular docking studies of new mono- and dispirocyclotriphosphazenes with pendant arm(s) - Iscan, Ozlem; Cemaloglu, Resit; Asmafiliz, Nuran; Zeyrek, Celal Tugrul; Kilic, Zeynel; Acik, Leyla; Aydin, Betul; İşcan, Özlem (Springer, 2022)
Mono-/dispirocyclotriphosphazenes with pendant arm(s) are robust, but they are less investigated inorganic ring systems. In this study, a series of mono (3 and 4)- and dispirocyclotriphosphazenes with 4-chloro-benzyl pendant arm(s) (13-16) was obtained from the Cl exchange reactions of hexachlorocyclotriphosphazene with sodium (N-benzyl)aminopropanoxides (1 and 2). When compound (3) reacted with excess pyrrolidine, morpholine, tetra-1,4-dioxa-8-azaspiro[4,5]decane (DASD) and piperidine, the fully substituted monospirocyclotriphosphazenes (7, 9, 10 and 12) occurred. But, the reactions of 4 with excess piperidine and morpholine produced the gem-piperidino (5)- and morpholino (6)-substituted monospirocyclotriphosphazenes, whereas the reactions of 4 with excess pyrrolidine and DASD gave the fully substituted monospirocyclotriphosphazenes (8) and (11). However, it should be indicated that these derivatives were obtained to be used for the investigation of their spectral, stereogenic and biological properties. The structures of 5, 7 and 14 were determined crystallographically. X-ray data of 5 and 14 displayed that both of compounds were chiral in solid state, and their absolute configurations were assigned as R and RR. Additionally, the antimicrobial activities of phosphazenes were investigated. Minimum inhibitory concentrations, minimal bacterial concentrations and minimum fungicidal concentrations of phosphazenes were determined. The interactions of phosphazenes with plasmid DNA were evaluated by agarose gel electrophoresis. The cytotoxic activities of compounds were studied against L929 fibroblast and DLD-1 colon cancer cells. In addition, density functional theory calculations of 5, 7 and 14 were reported, and their molecular docking studies with DNA, E. coli DNA gyrase and topoisomerase IV were presented.
Keywords: Mono; And Dispirocyclotriphosphazenes; Crystal Structure; Antimicrobial Activity; Cytotoxicity; Dft Calculations; Molecular Docking